PELATIHAN DAN PENDAMPINGAN PEMBUATAN SOAL PISA BERORIENTASI SSI (SOCIOSSCIENTIFIC ISSUES) GURU SDN 1 PAKISAJI GUNA PENINGKATAN KEMAMPUAN LITERASI SAINS - Pratika, Vindhy Dian Indah; Syafi’ah, Rohmatus; Permatasari, Faudina (Politeknik Perkeretaapian Indonesia Madiun, 2024)
The development of science and technology has an influence on various aspects of human life, such as competition in the social, industrial fields and the development of social life globally. The solution offered to face the development of science is to increase scientific literacy skills which are expected to be able to become the golden generation in modern society. Scientific literacy is important to explicitly integrate the aspects needed to develop science learning in schools. The target of this research is teachers at SDN 1 Pakisaji, Tulungagung, which was carried out on February 23 2024. The aim of this research is to provide training and assistance in making PISA questions oriented towards SSI questions so that they can improve the quality of teachers in scientific literacy. This research provides benefits for teachers in being able to broaden their horizons in presenting questions to students so that later with the SSI-oriented PISA questions, they can also help students in analyzing various kinds of questions and improve their analytical skills on questions.